Employing video-editing skill in designing materials for Speaking class - Marisa Yoestara; Nyak Mutia Ismail (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2022)
This study sought to prove whether there is an inclination in students’ ability before and after video-editing treatments.This study was carried out under the umbrella of quasi-experimental study as it involved one group pretes-posttest design. There were 13 students chosen through the procedure of total sampling. They were given a pretest to make 3 videos—3 minutes in duration each—in topic of Describing People, Inviting People, and Accepting and Refusing Invitation. Later, six treatments were given: three treatments of video-editing and three other were about material design. Afterwards, the post-test was essentially similar with pretest regarding the procedural means. The data were analyzed using SPSS 22 by employing the formula of normality test and Z-Score to perform hypothesis testing. The results uncovered that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is consequently accepted because the rvalue obtained from the Z-Score is 2.63, which is higher than rtable= 0.47 (df=11, α=0.05, right tailed). Additionlly, the average score for the 13 samples before applying video editing procedures was 56.23, and after the treatments, this score incilned to be 79.Then in can be concuded that after obtaining the treatments, students' performance in terms of video editing abilities with reference to material design or speaking class has necessarily improved. The finding implies that it is best to train teacher and prospective teachers with video-editing ability to enable them design good and convenient teaching materials in the future where digital era has transmerged into all pedagogical aspects.DOI: 10.26905/enjourme.v7i2.8817